Object Visibility, Not Energy Expenditure, Accounts For Spatial Biases in Human Grasp Selection. (February 2019) - Maiello, Guido; Paulun, Vivian C.; Klein, Lina K.; Fleming, Roland W.
Humans exhibit spatial biases when grasping objects. These biases may be due to actors attempting to shorten their reaching movements and therefore minimize energy expenditures. An alternative explanation could be that they arise from actors attempting to minimize the portion of a grasped object occluded from view by the hand. We reanalyze data from a recent study, in which a key condition decouples these two competing hypotheses. The analysis reveals that object visibility, not energy expenditure, most likely accounts for spatial biases observed in human grasping.